Genetic susceptibility in granulomatous disorders: chronic beryllium disease and sarcoidosis - Newman, Lee (Henry Stewart Talks, 2007)
Role of genetics x exposure in environmental lung disease, Granulomatous disorders and immunologic mechanistic basis: berylliosis and sarcoidosis, Immunogenetics that may apply generally to granulomatous disorders, Berylliosis: genetic epidemiology studies, functional genomics and gene x environment interaction studies, Role of exposure vs. genetic basis, Sarcoidosis: genetic epidemiology studies, attempts at functional genomics and directions for research to use clinical phenotype and genotype information to improve and help direct the search for an unknown causative agent, Possible implications for other (non-granulomatous) environmental lung disorders
Archived at 2015/09/08